Pengaruh Program Pendidikan dan Pelatihan Terhadap Produktivitas Kerja Karyawan di Dinas Pendidikan dan Kebudayaan Kabupaten Ogan Ilir - Sindi Nova; Heriyanto Heriyanto (Universitas Batanghari Jambi, 2023)
This study aims to determine how much influence the Education and Training Program has on Employee Work Productivity at the Education and Culture Office of Ogan Ilir Regency. This type of research used is quantitative data. The data collection technique uses a questionnaire, with 32 samples. The quantitative method is a research method that can be interpreted as a research method based on the philosophy of positivism. Data collection uses research instruments, data analysis is quantitative with the aim of testing established hypotheses. The results of the study show that education has a positive and significant effect and training has a positive effect, but partially all variables have an influence on work productivity. Education has a dominant influence, which also means that the hypothesis proposed is accepted.